Effect of tranexamic acid in spine surgeries: a systematic review and network meta-analysis - Shim, Sung Ryul; Han, Sangah; Jeong, Ji Hun; Hwang, Inhwan; Cha, Yonghan; Ihm, Chunhwa (Frontiers in Surgery, 2025)
BackgroundSevere blood loss during spine surgery increases the need for blood transfusion. Transfusion carries the risks of infection, complications, and postoperative morbidity; therefore, minimizing these risks is crucial for all surgical patients.MethodsA comprehensive literature search was conducted in PubMed, Cochrane, and EMBASE to find studies examining the effect of tranexamic acid (TXA) on spine surgeries in patients who received blood transfusion. We used the mean difference (MD) and 95% credible intervals (CrI) to analyze continuous outcomes, such as intraoperative blood loss, postoperative blood loss, hemoglobin drop, and length of hospital stay. To evaluate categorical outcomes, such as blood transfusion rate and complication rate, the odds ratios (OR) and 95% CrI were determined.ResultsA total of 38 randomized controlled trials were included, evaluating six outcomes across 10 treatment groups. Low-dose intravenous (IV) TXA combined with temperature intervention (15 mg/kg) significantly reduced intraoperative blood loss compared with placebo [MD: −112.0; 95% CrI: −211.0 to −14.9, surface under the cumulative ranking curve (SUCRA): 78.37%]. The administration of more than two doses of TXA significantly reduced intraoperative blood loss (MD: −101.0, 95% CrI: −161.0 to −44.1, SUCRA: 77.65%) and postoperative blood loss (MD: −177.0, 95% CrI: −275.0 to −92.4, SUCRA: 85.66%) compared with placebo. Both treatments significantly impacted the hemoglobin drop and blood transfusion rate.ConclusionsLow-dose IV TXA with temperature intervention and the combined use of TXA significantly improved blood loss, hemoglobin drop, and blood transfusion rate during spine surgeries. Further studies involving larger populations are warranted and should be carefully designed to determine the potential risk of complications.Systematic Review Registrationwww.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024531557, identifier: CRD42024531557.